Two-step temperature deposited FePt bilayer for tunable magnetic properties - Dutta, Tanmay (2015)
Tuning the magnetic properties of FePt media is of great interest in the bid to achieve high areal densities. In this work, we demonstrate that properties of FePt media can be tuned using a two-step temperature deposited FePt bilayer. In this bilayer scheme, the first layer of FePt was deposited at a high nominal temperature (600 °C), whilst the second layer was deposited at a lower temperature over the first layer. This resulted in tunable magnetic and improved topographical properties, and was due to the interplay of a number of temperature-dependent factors such as epitaxial growth, new grain nucleation, surface mobility, and difference in the thermal expansion coefficients. Transmission electron microscopy imaging was used to understand the growth dynamics of the second FePt layer in the two-step temperature deposited structures.